Geometrical and dimensional defect evaluation of cold forged AA6061 propeller blade - Abdullah, Ahmad Baharuddin (2013)
Accuracy is a key issue in cold forging process. Component defect is one of the major problems in cold forging because the process depends on many factors including complexity of the component. Defect not only affects the performance of the component but may also harm the assembly. The problem of defect becomes more critical as the complexity of the component increases, but the size and complexity of the part limit the effective assessment of the defect. This project aims to investigate the geometrical and dimensional defects that occur in Autonomous Underwater Vehicle propeller blades produced using the cold forging process. Typically the manufacturing of the blade can be divided into five stages namely, blanking,forming, trimming, heading and twisting. The defect was evaluated based on the three main criteria of the blade. First, the overall geometrical and dimensional accuracy of the blade was measured. In this study, the profile of the forged blade was considered as the final part, whereas the profile obtained from the punch was considered as the targeted profile. The profile was captured using a commercial focus variation based 3D surface measurement system, the Infinite Alicona System. The constructed 3D profile was then compared to a nominal model. Next, the filling ability of the pin head during the cold embossing or heading process was investigated,because an imperfect or defective pin head may affect the final assembly of the blade. In this work, the effects of design and process parameters, including punch diameter and distance to edge on the formation of defect, were studied using the commercial 2D finite element analysis software DEFORM-2D. The defect can be estimated based on the incomplete filling of the region and the amount of bulging based on the captured images of the simulation result. In addition, the defect was predicted by investigating the design parameters and its effect on the material flow pattern. Comparison between the simulation result and the fabricated pin head show a geometrically similar pattern. Finally, the twist springback was measured. In this study,defect was considered based on profile deviation, which was obtained from the 3D surface measurement technique. An algorithm was developed to measure the deviation. The result showed that the thickness error depended on the deformation ratio whereas the twist angle accuracy relied on the amount of twist and thickness of the blade. In the other case, the simulation results indicated that the most significant parameter for the filling ability and amount of bulging was the distance to edge, whereas the punch taper was not relevant for cases of edge embossing. In the case of twist springback, the results implied that the twist springback increased as the twist angle increased. The highest springback was found to be at 16.11% for section E, while the lowest is 2.58% for section A. Similarly, the twist springback increased with the increase in deformation ratio. The coordinate measurement machine was used to validate the result. This study will contribute to the development of effective evaluation method in the noncontact measurement of geometrical and dimensional defect of component with complex profile such as the propeller blade.